Death Anxiety Scale for Pre-Surgical Patients - Khan, Rabia Noor; Dar, Rafiq (Pakistan Armed Forces Medical Journal, 2022)
Objective: To develop a scale for assessing death anxiety in pre-operative patients.Study Design: Cross sectional study.Place and Duration of Study: District Head Quarters Gujranwala, Fazal Hospital Gujranwala, Gondal Hospital Gujranwala and Mayo Hospital, Lahore Pakistan, from Apr to Nov 2020.Methodology: Three hundred and fifty patients were included in the study. The one-factor solution was run on the data as the data was homogenous, and multiple factors were not elicited. The severity level of the patients’ symptoms was explored using the subjective rating scale. The developed scale's validity was compared with the translated Arabian version of death anxiety.Results: Varimax rotation and scree plot showed that one component solution best fit the indigenously developed scale. The severity level of the patients on the subjective rating scale for each item showed that patients in Pakistani culture would face more psychosomatic symptoms of death anxiety rather than emotional ones.Conclusion: The indigenously developed scale would help manage pre-surgical patients' psychosomatic symptoms of death anxiety.